Resistance Test of Fast Patrol Ships in the Islands of Indonesia - Rizal, Nandiko (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2018)
This paper is researching about the results of the resistance test from fast patrol ships in Indonesia. The test itself describes a series of resistance test of the Fast Patrol Ship model in a Towing Tank. The test has a purpose to predict the resistance and effective horsepower (EHP) of a ship at a certain speed on various knots. Resistance test is done at full load condition, and by making model of ship with scale which is adjusted with Towing Tank capacity at Indonesia Hydrodynamics Laboratory (IHL) - BPPT. The testing itself will use various equipment and instruments such as Trim Meter and Data acquisition tools. The shape and dimension of the model are based on the client’s lines plan and are made of fiberglass / laminated wood. The results are presented in curve form describing the relationship between the velocity of the vessel to the total ship resistance and the ship effective power (EHP) in knots and Kilowatts unit